1984
DOI: 10.1107/s0108768184002007
|View full text |Cite
|
Sign up to set email alerts
|

The low-temperature phase of sodium azide

Abstract: The low-temperature phase of sodium azide has been studied at a number of temperatures between 12 and 293 K using a combination of single-crystal and powder X-ray techniques. The structure is monoclinic with space group C2/m. The unit cell undergoes a discontinuous shear of 0.5 ° in the ac plane from the rhombohedral (R3m) structure at the transition temperature (292.2 K), and this is followed by a continuous change amounting to a total shear of 5-3 ° at 12 K. The unit-cell dimensions at 12 K are a= 6.1654 (5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…[12][13][14] Metal azides undergo a variety of pressure or temperatureinduced phase transitions, a phenomenon which has been intensively studied. [14][15][16][17][18][19][20][21][22][23][24][25] The behavior of the azide anions (N 3 À ) during the phase transition is noticeable. In the temperatureinduced tetragonal-cubic phase transitions of both rubidium azide (RbN 3 ) and cesium azide (CsN 3 ), a fluctuation of the orientation of N 3 À anions was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Metal azides undergo a variety of pressure or temperatureinduced phase transitions, a phenomenon which has been intensively studied. [14][15][16][17][18][19][20][21][22][23][24][25] The behavior of the azide anions (N 3 À ) during the phase transition is noticeable. In the temperatureinduced tetragonal-cubic phase transitions of both rubidium azide (RbN 3 ) and cesium azide (CsN 3 ), a fluctuation of the orientation of N 3 À anions was observed.…”
Section: Introductionmentioning
confidence: 99%
“…1). The structure of the α-form was later confirmed by a combination of X-ray single-crystal and powder diffraction [12].…”
Section: Introductionmentioning
confidence: 91%
“…At the same time, Hirotsu's study of the birefringence of a single crystal also gave clear evidence for a first order transition [20]. These contemporaneous results had a significant impact on opinion in the literature -subsequent observations have been contextualised using models that emphasise the displacive nature of the transition [21][22][23][24] Careful measurements of the unit cell parameters and symmetry-breaking shear strains as a function of temperature between 12 and 295 K confirmed that the transition involves a coupling of the canting of the azide anion (order-disorder) with the shearing of the sodium layers (displacive) [12]. This is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 91%
“…The crystallographic structures of both forms of NaN 3 have been determined through use of both x-ray and neutron diffraction, [8] and they are related in such a way that a continuous interchange between the structures is possible and the heatcapacity curve near the transition is -type. Of four studies that have investigated the nature of the transition, one [9] called it second order, another [10] called it weakly first order, and two [11,12] called it predominantly second order. Three reports [13][14][15] for ⌬ t H gave values varying between ∼0.01 and ∼0.1 kJ/mol, but these indications that ⌬ t H 0 were apparently based on the integration of heat-capacity curves and may be indicative of the energy of randomization that is distributed over a temperature range preceding the transition and thus are not a valid proof of a first-order transition.…”
Section: Complicationsmentioning
confidence: 99%